The difficulties experienced in patient communication by nursing students taking the clinical practice course for the first time – a qualitative study - Harmanci, Pinar (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Nursing fields begin to face a wide variety of challenges when they first enter clinical practice. The aim of this study is to determine the difficulties experienced in patient communication by nursing students taking the clinical practice course for the first time Material and methods. Focus group interview design was used for this study. Focus group design is used to give information about the opinions and experiences of the sample group on any subject. It is reported as a convenient design to identify different perspectives on a subject within the scope of the sample. Focus group interviews are a widely used method as data collection technique. Results. The findings of the study continue on 4 main themes at level 3, by identifying the similarities and differences in the codes determined by the three experts (researchers consulted and the researcher conducting/reporting the study). The findings of the study were evaluated in comparison with the findings of the studies reached in the literature and conducted in regions such as Israel, Iran, Sri-Lanka, Kenya, and Africa. Conclusion. There are many problems in student-patient communication in many different dimensions. The difficulties arising due to these problems generally focus on unknown clinical environment, lack of knowledge, differences between theory and practice, and mentor interaction.
The ethical permission of the study, numbered 07-22 and dated 30.03.2022, was obtained from Tokat Gaziosmanpaşa University Scientific Research and Publication Ethics. Before this permission, written study permission was obtained from the school of the nursing students where the study would be conducted. The participants were informed verbally and the Helsinki declaration was read to each of them. Informed consent was signed by the participants.
Keywords: difficulties first practice; nursing students; patient communication